A comparison of intestinal microbiota in a population of low-risk infants exposed and not exposed to intrapartum antibiotics: The Baby & Microbiota of the Intestine cohort study protocol. Issue 1 (December 2016) - Simioni, Julia; Hutton, Eileen; Gunn, Elizabeth; Holloway, Alison; Stearns, Jennifer; McDonald, Helen; Mousseau, Andrea; Schertzer, Jonathan; Ratcliffe, Elyanne; Thabane, Lehana; Surette, Michael; Morrison, Katherine
Abstract Background The intestinal microbiota influences metabolic, nutritional, and immunologic processes and has been associated with a broad range of adverse health outcomes including asthma, obesity and Type 2 diabetes. Early life exposures may alter the course of gut microbial colonization leading to differences in metabolic and immune regulation throughout life. Although approximately 50 % of low-risk full-term infants born in Canada are exposed to intrapartum antibiotics, little is known about the influence of this common prophylactic treatment on the developing neonatal intestinal microbiota. The purpose of this study is to describe the intestinal microbiome over the first 3 years of life among healthy, breastfed infants born to women with low-risk pregnancies at full term gestation and to determine if at 1 year of age, the intestinal microbiome of infants exposed to intrapartum antibiotics differs in type and quantity from the infants that are not exposed. Methods A prospectively followed cohort of 240 mother-infant pairs will be formed by enrolling eligible pregnant women from midwifery practices in the City of Hamilton and surrounding area in Ontario, Canada. Participants will be followed until the age of 3 years. Women are eligible to participate in the study if they are considered to be low-risk, planning a vaginal birth and able to communicate in English. Women are excluded if they have a multiple pregnancy or a preterm birth. Study questionnaires are completed, anthropometric measures are taken and biological samples are acquired including eight infant stool samples between 3 days and 3 years of age. Discussion Our experience to date indicates that midwifery practices and clients are keen to participate in this research. The midwifery client population is likely to have high rates of breastfeeding and low rates of intervention, allowing us to examine the comparative development of the microbiome in a relatively healthy and homogenous population. Results from this study will make an important contribution to the growing understanding of the patterns of intestinal microbiome colonization in the early years of life and may have implications for best practices to support the establishment of the microbiome at birth.